Barriers to men's involvement in antenatal and postnatal care in Butula, western Kenya - Fernandos K. Ongolly; Salome A. Bukachi (AOSIS, 2019)
Background: Men have a lot of influence on their partners' and children's health. However, studies have shown their involvement in antenatal care (ANC) and postnatal care (PNC) is relatively low owing to several factors. Aim: To explore the barriers to men's involvement in ANC and PNC in Butula sub-county, western Kenya. Setting: Butula sub-county, Busia county, western Kenya. Methods: A mixed methods study design, descriptive in nature, was used to collect both quantitative and qualitative data. A total of 96 men were selected to participate in the surveys. Also, four focus group discussions and four key informant interviews were conducted. Results: We found out that some men still participate in ANC and PNC despite the barriers. The perception that maternal health is a women's domain and existence of alternative traditional maternal services were key cultural barriers. The men's nature of work, low income and expenses incurred at ANC/PNC clinics were significant economic barriers. The lack of services targeting men, provider attitude, non-invitation to the clinic, time spent at the clinic and lack of privacy at the clinics were key facility-based barriers. Conclusion: A myriad of cultural, economic and health-facility barriers hinder men from active involvement in ANC and PNC. Awareness creation among men on ANC and PNC services and creating a client-friendly environment at the clinics is key in enhancing their involvement. This should be a concerted effort of all stake holders in maternal health services, as male involvement is a strong influencer to their partners' and children's health outcomes.